Empirical study on video clip consumption: Focusing on viewing habits and use motives - Ji Young Lee; Min Jeong Ham; Sang Woo Lee (International Telecommunications Society (ITS), 2018)
As TV viewing on mobile devices increases, Korean broadcasters provide video clips that are made by re-editing the length or format of existing broadcast content. Traditional broadcasters and cable networks provide the edited video clips of their full live programs for free. The number of video clips for each live program is different, but generally 5 to 10 video clips for each live program are provided via online or mobile. understand the behavior of video clip consumers. This study is to understand the behavior of video clip consumers. We tried to examine how video clip consumers use video clip services according to their preferences and viewing habits. This study also aims to investigate the reason why Korean people watch short clips of television content. This study investigated the relationship between video clip use motives and actual usage of video clips. To analyze additional promotional effect of video clips, this study explore what motives are related to the intention to watch the live programs and to purchase VOD.
Keywords: 330; TV viewing; mobile device; video clips; live programs; VOD